ANALYSIS OF TURNOVER INTENTION THROUGH ORGANIZATIONAL COMMITMENT AT PT. BANK CIMB NIAGA - Emi Wakhyuni; Husni Muharram Ritonga; Khairil Husnizar (CV. Radja Publika, 2024)
In this study, structural equation modeling is used to analyze the relationship between organizational culture, leadership and job satisfaction on Turnover Intention through organizational commitment. The method used in collecting data is a quantitative method supported by SEM. Data were collected by distributing questionnaires to employees at CIMB Niaga by analyzing the data using the SEM method with the help of AMOS 22 software. SEM analysis has seven stages, namely, (1) development of theoretical models, (2) development of path diagrams, (3) conversion of path diagrams to structural equations, (4) selecting input matrices and types of estimation, (5) identifying models, (6) assessing goodness of fit criteria, (7) interpreting results. Based on the results of the study, it shows that organizational culture and leadership do not significantly affect Turnover Intention, satisfaction does not significantly affect Turnover Intention, organizational culture and leadership have a significant effect on commitment, job satisfaction has a significant effect on commitment, commitment has a significant effect on Turnover Intention and organizational culture, leadership and satisfaction have a significant effect on Turnover Intention through commitment as a mediating variable.